2001
DOI: 10.1097/00004872-200111000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors in normotensive and hypertensive Egyptians

Abstract: This is one of the few reports on the prevalence of cardiovascular risk factors in a developing country. Risk factors cluster with rising level of BP and with ageing. Obesity is very prevalent, particularly in hypertensive Egyptian women. Health efforts directed at the prevention and treatment of obesity should be a high priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
14
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 21 publications
5
14
0
Order By: Relevance
“…The positive association between obesity and hypertension observed in our study has been reported in numerous studies [8,[10][11][12]14,16,19,25,26]. The Framingham study indicated that 70% of new-onset hypertension may be attributed to obesity or weight gain [25].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The positive association between obesity and hypertension observed in our study has been reported in numerous studies [8,[10][11][12]14,16,19,25,26]. The Framingham study indicated that 70% of new-onset hypertension may be attributed to obesity or weight gain [25].…”
Section: Discussionsupporting
confidence: 85%
“…In our study, smoking was not a significant risk factor for hypertension. A similar result was found in the study of Mohsen Ibrahim in Egypt [16]. Certain studies indicate that smokers and ex-smokers are more at risk [17][18][19].…”
Section: Discussionsupporting
confidence: 84%
“…Key Words obesity, dyslipidemia, resting energy expenditure , dietary factors Obesity can have many negative effects on health, and is associated with diabetes (1), cardiovascular dis ease (2), hypertension (3), osteoarthritis (4) and dyslipi demia (5). Studies conducted in Sub-Saharan Africa have reported an increase in the prevalence of obesity among both men and women in urban areas (6,7). Other epidemiological surveys in developing countries have shown that an unhealthy diet contributes to the increasing problem of obesity (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…The survey was conducted in 21 sampling locations in six Egyptian governorates, representing all Egypt's geographic areas and socioeconomic groups. The details of sample design, field operations, and technique for blood pressure measurements, laboratory tests and echocardiographic examination were reported in previous publications (9)(10)(11).…”
Section: Study Populationmentioning
confidence: 99%